Rijksaankopen 1984 : Werk van hedendaagse beeldende kunstenaars. - Beer, Evelyn; de Haas, Robert; van Burkom, Frans; van Straaten, Evert; van Tuyl, Gijs (Den Haag : RBK (Rijksdienst Beeldende Kunst), 1985)
Abramovic, Marina & Ulay ; Akkerman, Ben ; Andriesse, Erik ; Appel, Karel ; Appenzeller, Hans ; Armando ; van den Assem, Marjolijn ; van Bakel, Gerrit ; Bannenberg, Peggy ; Blok, Diana ; Boers, Jan ; Boeyen, Mari ; Bogart, Bram ; van Bohemen, Kees ; Boogaard, Bert ; Bot, Marrie ; Brand, Dicky ; van den Broeck, Frank ; Broek, René Van Den ; Brusse, Mark ; Buisman, Sjoerd ; Cassée, Dick ; Claassen, Johan ; Constant ; Copier, A.D. ; Defesche, Pieter ; Dekkers, Ger ; van Delft, Jan ; Derks, Sandra ; Dibbets, Jan ; Dieleman, Piet ; van Dijk, Paul ; Dilworth, Norman ; van den Dobbelsteen, Jan ; van Domburg, Cor ; Domela-Nieuwenhuis, César ; Dumas, Marlene ; Ebeling Koning, Hans ; van Elk, Ger ; van Elk, Maria ; van den Ende, Jaap ; Engels, Pieter ; Ernie+Bidet ; Fortuyn/O'Brien ; Freijmuth, Alphons ; Geerdink, Herman ; Van Geest, Arie ; Geraedts, Pieter ; Geraedts, Thom ; Gerritsen, Ad ; Geurts, Joris ; de Goey, Marijke ; Graevenitz, Gerhard von ; Groen, Daniël ; Groot, David ; Gubbels, Klaas ; van der Haak, Christie ; Hansma, Siebe ; Hazenbroek, Ernest ; Heiden, Cécile Van Der ; Henderikse, Jan ; Herbst, Marion ; Heyboer, Anton ; Holstein, Pieter ; van Holten, Bob ; Hooykaas, Madelon ; van der Horst, Loes ; van den Houten, Hans ; Izaks, Wim ; Janselijn, Han ; Kaap, Gerald Van Der ; Kalksma, Gea ; van Kesteren, Maria ; van Keulen, Floor ; Koch, Pyke ; van Koningsbruggen, Rob ; Kooi, Hans ; Koolhaas, Rem ; de Kop, David van ; Körmeling, John ; Krzyzanowski, Michel Szulc ; Kuijpers, Theo ; Lap, Geert ; van Leersum, Emmy ; van Leeuwen, Piet ; Leideritz, Guus ; Lichtveld, Alexander ; van Lieshout, Jeanny ; Liggins, John ; Lion, Dick ; Lucassen ; Lucebert ; Makkink, Herman ; Malewicz, Monika ; Mantje, Aldert ; Marinus, Boezem ; Mark, Arno Van der ; etc.
Rijksaankopen 1984 : Werk van hedendaagse beeldende kunstenaars. RBK (Rijksdienst Beeldende Kunst) 's-Gravenhage - Amsterdam, 23.05.1985 - 28.07.1985
Nederlands
boek